TELAAH TERHADAP POLIGAMI DALAM PERSPEKTIF HUKUM ISLAM - Ahmad Zahari (Faculty of Law, Universitas Diponegoro, 2014)
Polygamy, to the Indonesian Muslims, still has polemic, both the institution and the arrangement. The interpretation of polygamy is still explicit and partial, the positive side being supressed and the negative being exposed or otherwise. Consequently, polygamy has excessively and irresponsibly been practiced, deviating from the regulations, and to some people it is something frightening and should be abolished or avoided. This research discusses polygamy from a wider, comprehensive, objective, responsible and rational perspective in accordance with its main purpose. Hopefully, polygamy can contribute significantly to the lives of the individual, family, community, nation and state